B-Box Containing Proteins BBX30 and BBX31, Acting Downstream of HY5, Negatively Regulate Photomorphogenesis in Arabidopsis . Issue 1 (14th February 2019) - Heng, Yueqin; Lin, Fang; Jiang, Yan; Ding, Mingquan; Yan, Tingting; Lan, Hongxia; Zhou, Hua; Zhao, Xianhai; Xu, Dongqing; Deng, Xing Wang
Abstract : Two repressors of light signaling, BBX30 and BBX31, are transcriptionally and negatively regulated by the transcription factor HY5 through direct binding to the G-box cis-element present in their promoters. Abstract: Light-mediated seedling development is coordinately controlled by a variety of key regulators. Here, we identified two B-box (BBX)-containing proteins, BBX30 and BBX31, as repressors of photomorphogenesis. ELONGATED HYPOCOTYL5, a central regulator of light signaling, directly binds to the G-box cis- element present in the promoters of BBX30 and BBX31 and negatively controls their transcription levels in the light. Seedlings with mutations in BBX30 or BBX31 are hypersensitive to light, whereas the overexpression of BBX30 or BBX31 leads to hypo-photomorphogenic growth in the light. Furthermore, transgenic and phenotypic analysis revealed that the B-box domain of BBX30 or BBX31 is essential for their respective functioning in the regulation of photomorphogenic development in plants. In conclusion, BBX30 and BBX31 act as key negative regulators of light signaling, and their transcription is repressed by ELONGATED HYPOCOTYL5 through directly associating with their promoters.